Pharmacogenetics of antiemetics for chemotherapy-induced nausea and vomiting: A systematic review and meta-analysis. (May 2020) - Eliasen, Astrid; Dalhoff, Kim; Mathiasen, René; Schmiegelow, Kjeld; Rechnitzer, Catherine; Schelde, Astrid Blicher; Perwitasari, Dyah Aryani; Tsuji, Daiki; Brok, Jesper
Graphical abstract: Highlights: Nausea and vomiting are common side effects of chemotherapy. The severity of nausea and vomiting varies substantially among cancer patients. Polymorphisms in ABCB1 and HTR3C are associated with the risk of nausea/vomiting. The data on polymorphisms is still insufficient to allow clinical implementation. Abstract: A substantial proportion of cancer patients experience chemotherapy-induced nausea and vomiting (CINV) despite the use of antiemetic drugs. Prevalent genetic polymorphisms involved in antiemetic drug metabolism, drug transport and receptor pathways likely affect the effectiveness of antiemetics. Knowledge on which polymorphisms to integrate into individualised clinical care is needed. We did a systematic review evaluating the association between polymorphisms and effectiveness of antiemetics in cancer patients receiving moderately to highly emetogenic chemotherapy. Twenty studies n = 2331 evaluated eight polymorphisms in five candidate genes involved in 5-HT3 antagonist pathways. HTR3C C1214G increased the risk of acute chemotherapy-induced vomiting in the dominant model (odds ratio (OR) = 2.67, 95 % confidence interval (CI): 1.08–6.63). ABCB1 C3435T reduced the risk of acute CINV in the recessive model (OR = 0.60, 95 % CI: 0.44-0.81). Future studies should evaluate candidate genes that affect pharmacogenetics of other antiemetics beside 5-HT3 antagonists.